Factors Associated with Impaired Cognitive Function in the Elderly People (Jurnal Ilmu Kesehatan Masyarakat, 2022)
The decline in cognitive function that occurs in the elderly can result in limitations in carrying out daily work, making dependence on others so that it can reduce the quality of life. The purpose of this study was to identify cognitive function disabilities and the factors that influence cognitive function diseases in the elderly in RW 01 Kelurahan Susukan Kecamatan Ciracas, East Jakarta. This study uses a quantitative method through a cross- sectional approach. The population in this study were the elderly aged ≥ 60 years, amount to 386 people. The research sample was 197 people. The independent variables in this study were age, gender, education level, history of degenerative diseases and physical activity and the dependent variable was cognitive function in the elderly. The data was collected using the MMSE (Mini Mental State Examination) and IPAQ (International Physical Activity Questionnaire) questionnaires. Data analysis was carried out by univariate, bivariate with Chi Square test and multivariate with multiple logistic regression test predictive model. The results of the study with variables that had a significant relationship were education level variables (p-value = 0.000), history of degenerative diseases (p-value = 0.019) and physical activity (p-value = 0.000). Variables that did not have a significant relationship with cognitive function were age (p-value=0.190 and gender (p-value=1,000). The results showed that most of the elderly had normal cognitive function and there was a relationship between the level of education, history of degenerative diseases and physical activity with the cognitive function of the elderly. Future research is expected to be able to conduct studies that focus more on a more diverse educational background and develop its relationship with cognitive and dementia incidence.